Role of Barrier Integrity and Dysfunctions in Maintaining the Healthy Gut and Their Health Outcomes - Panwar, Shruti; Sharma, Sapna; Tripathi, Prabhanshu (Frontiers in Physiology, 2021)
Mucosal surface layers are the critical borders throughout epithelial membranes. These epithelial cells segregate luminal material from external environments. However, mucosal linings are also accountable for absorbing nutrients and requiring specific barrier permeability. These functional acts positioned the mucosal epithelium at the epicenter of communications concerning the mucosal immune coordination and foreign materials, such as dietary antigens and microbial metabolites. Current innovations have revealed that external stimuli can trigger tseveral mechanisms regulated by intestinal mucosal barrier system. Crucial constituents of this epithelial boundary are physical intercellular structures known as tight junctions (TJs). TJs are composed of different types transmembrane proteins linked with cytoplasmic adaptors which helps in attachment to the adjacent cells. Disruption of this barrier has direct influence on healthy or diseased condition, as barrier dysfunctions have been interrelated with the initiation of inflammation, and pathogenic effects following metabolic complications. In this review we focus and overview the TJs structure, function and the diseases which are able to influence TJs during onset of disease. We also highlighted and discuss the role of phytochemicals evidenced to enhance the membrane permeability and integrity through restoring TJs levels.